Imaging oxidative stress in brains of chronic methamphetamine users: A combined 1H-magnetic resonance spectroscopy and peripheral blood biomarker study - Watling, Sarah E.; Jagasar, Samantha; McCluskey, Tina; Warsh, Jerry; Rhind, Shawn G.; Truong, Peter; Chavez, Sofia; Houle, Sylvain; Tong, Junchao; Kish, Stephen J.; Boileau, Isabelle (Frontiers in Psychiatry, 2023)
Preclinical data suggest methamphetamine (MA), a widely used stimulant drug, can harm the brain by causing oxidative stress and inflammation, but only limited information is available in humans. We tested the hypothesis that levels of glutathione (GSH), a major antioxidant, would be lower in the brains of chronic human MA preferring polysubstance users. We also explored if concentrations of peripheral immunoinflammatory blood biomarkers were related with brain GSH concentrations. 20 healthy controls (HC) (33 years; 11M) and 14 MA users (40 years; 9M) completed a magnetic resonance spectroscopy (MRS) scan, with GSH spectra obtained by the interleaved J-difference editing MEGA-PRESS method in anterior cingulate cortex (ACC) and left dorsolateral prefrontal cortex (DLPFC). Peripheral blood samples were drawn for measurements of immunoinflammatory biomarkers. Independent samples t tests evaluated MA vs. HC differences in GSH. GSH levels did not differ between HC and MA users (ACC p=0.30; DLPFC p=0.85). 17 of 25 immunoinflammatory biomarkers were significantly elevated in MA users and matrix metalloproteinase (MMP)-2 (r=0.577, p=0.039), myeloperoxidase (MPO) (r=-0.556, p=0.049), and MMP-9 (r=0.660, p=0.038) were correlated with brain levels of GSH. Normal brain GSH in living brain of chronic MA users is consistent with our previous postmortem brain finding and suggests that any oxidative stress caused by MA, at the doses used by our participants, might not be sufficient to cause either a compensatory increase in, or substantial overutilization of, this antioxidant. Additionally, more research is required to understand how oxidative stress and inflammatory processes are related and potentially dysregulated in MA use.